Le Bassin parisien. Une région métropolitaine - Frédéric Gilli (Cybergeo, 2005)
The Greater Paris area has a direct influence over its administrative boundaries. It constitutes an integrated metropolitan area. Figures such as the commuting pattern or the presence of integrated firms are convincing proofs of the existence of a huge economically integrated and functional region.Besides, the industrial pattern shows a vast and complex organisation made of functional and sector complementarities (companies are spread over the basin, places are specialized, activities are concentrated). If there are specific patterns at a local level, the regional organisation is to be noticed. Hence, due to sector specialisations the Parisian basin is not hierarchical.